INTERAKSI SOSIAL PADA REMAJA PUTUS SEKOLAH DI DESA OMBAY KECAMATAN PANTAR TIMUR KABUPATEN ALOR - Hasruddin Nur; Hasanudin Kasim (Universitas Negeri Makassar, 2023)
This study aims to examine and describe the social interactions of out-of-school adolescents in Ombay Village Pantar Timur District, Alor Regency. The approach used in this research is descriptive qualitative. The focus of this study was adolescents who dropped out of school and their parents of adolescents who dropped out of school in Pantar Timur District, Alor Regency. The number of informants was 6 people using the snowball sampling technique. Data collection techniques used were observation, interviews and documentation. Data analysis technique is by using data collection, data reduction, data presentation and drawing conclusions. The validity of the data in this study was carried out through internal validation (credibility), dependability (defendability) and certainty of objectivity (confirmability). The results showed that the social interaction of dropout adolescents in Ombay Village Pantar Timur District, Alor Regency, namely the lack of interaction between children and their family and social environment, so that the interaction between parents and children was less than optimal, another reason for dropping out of school was joining in with their playmates. who is a school dropout, so the child is suggested by the condition of his friends.Penelitian ini bertujuan untuk mengkaji dan mendeskripsikan interaksi sosial remaja putus sekolah di Desa Ombay Kecamatan Pantar Timur Kabupaten Alor. Pendekatan yang digunakan dalam penelitian ini yaitu kualitatif deskriptif. Fokus penelitian ini adalah remaja putus sekolah dan orang tua remaja putus sekolah di Kecamatan Pantar Timur Kabupaten Alor.Jumlah informan berjumlah 6 orang dengan menggunakan teknik snowball sampling.Teknik pengumpulan data yang digunakan adalah pengamatan, wawancara dan dokumentasi. Teknik analisis data yaitu dengan menggunakan pengumpulan data, reduksi data, penyajian data dan penarikan kesimpulan. Pada keabsahan data dalam penelitian ini dilakukan melalui validasi internal (credibility), Kebergantungan (defendability) dan kepastian objektivitas (confirmability).Hasil penelitian menunjukan bahwainteraksi sosial remaja putus sekolah di Kecamatan Pantar Timur Kabupaten Alor yaitu kurang terjalin interaksi antara anak dengan lingkungan keluarga dan sosialnya, sehingga interaksi antara orang tua dan anak yang kurang maksimal, penyebab lainnya anak putus sekolah adalah ikut-ikutan bersama teman bermainnya yang merupakan anak putus sekolah, sehingga anak tersugesti dengan keadaan temannya.